HUBUNGAN DUKUNGAN SOSIAL DENGAN CITRA TUBUH PADA REMAJA PENGGUNA SOSIAL MEDIA DI SMA NEGERI 9 PALEMBANG - Fitri Yanti Mutmainah; Rina Oktaviana (Journal of Innovation Research and Knowledge, 2024)
This study aims to describe and explain the “relationship of social support with body image in social media teenagers in 9 Palembang State High School." The dependent variable used in the research is the body image, with a measurement scale referring to the aspects presented by Cash and Pruzinksy (2002). While the independent (free) variable of the study is social support, the measuring scale refers to those aspects proposed by Sarafino. (2011). The sample technique used is purposive sampling. The subjects of the study were adolescent students of the X and XI classes with the age range of 15-19 years and are active users of social media, followed by the number of students of the X class and XI. The total student population was 712 with a total sample of 88 students. Data compilation using a questionnaire with a Likert measurement scale. Data quality testing is carried out through validity testing and reliability testing. Classical assumption testing is done with normality testing, linearity unification, and hypothesis testing. The results of the research showed that there was a positive and significant relationship between social support and body image, and there is a link between social backing and body images in the students of X grade and 9th grade in Palembang